Design of Tactical Multipurpose All–Terrain Mobile Robot - Ranjan, Rahul; Lee, Seungjae; Kye, Joongeup (International Journal of Membrane Science and Technology, 2023)
Robotic systems that can assist soldiers in dangerous operations are essential technologies that improve safety and efficiency. This paper presents the development of mobile robots that can assist soldiers with target acquisition and surveillance on the battlefield. We have built a prototype that incorporates a firearm system that can perform shooting tasks. Our aim is to design and develop mobile robots that can cope with challenging scenarios such as terrorist attacks and rescue missions. Our robots can transmit photographic images or live streaming via a spy camera, and based on the visual information, soldiers can fire at their target with a gun mounted on the robot. We discussed the key technologies needed to design and manufacture such combat robots. Existing high-specification combat robots are expensive and inaccessible to students and researchers interested in the field. This paper reveals the technologies to develop a low-cost combat robot. This system can be used for real-time applications at an affordable price by using more advanced technology to improve its accuracy.